Dynamics of Surface Heating and Quenching of Titanium by a Submillisecond Intense Electron Beam - Teresov A. D. Anton; Koval T. V. Tamara Vasilievna; Moskvin P. Pavel; Chan Mi Kim An; Koval N. N. Nikolay Nikolaevich (2018, 2018)
Title screen